2000
DOI: 10.1177/096120330000900111
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjoögren's syndrome in men: clinical and immunological characteristics

Abstract: Although primary SS is typically a disease of middle-aged women, clinicians should note that it may be diagnosed in male patients. Except for a lower prevalence of articular involvement, we could no find any notable differences in clinical and immunological characteristics between male and female patients with primary SS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 12 publications
2
37
2
Order By: Relevance
“…Many studies have reported anti-SSA to be lower in men with primary SS, however a majority of studies have not found a consistent difference in serological status between men and women. [7][8][9][10][11][27][28][29][30] Also, we compared the proportion of seropositivity for either anti-SSA, anti-SSB, and/or ANA by gender, which has not been done before. Interestingly, men were four times more likely to be negative for all three tests compared to women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported anti-SSA to be lower in men with primary SS, however a majority of studies have not found a consistent difference in serological status between men and women. [7][8][9][10][11][27][28][29][30] Also, we compared the proportion of seropositivity for either anti-SSA, anti-SSB, and/or ANA by gender, which has not been done before. Interestingly, men were four times more likely to be negative for all three tests compared to women.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported men to have a lower prevalence of positive serologic tests (such as anti-SSA and anti-SSB); however, there is no clear consensus regarding the frequency of extraglandular manifestations by gender. [7][8][9][10][11] Despite the higher incidence rate of SS in women, the mortality rate has been noted to be almost three times higher in men compared to women. 12 This disparity in the severity of clinical manifestations may be due to gender differences in the pathophysiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Six studies were performed on men with previous pSS criteria over the past 20 years with very different results (8)(9)(10)(11)(12)(13). Except for a lower prevalence of articular involvement, Cervera et al (8) could not find any notable differences in clinical and immunological characteristics between 19 male and 204 female patients with pSS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have tackled this problem with results that are controversial because of the small number of patients studied or to the different classification criteria applied (8,10). We also studied the impact of gender on the time of appearance of new systemic involvement.…”
mentioning
confidence: 98%
See 1 more Smart Citation